Price reviews and arbitrations in Asian LNG markets - Ason, A (Oxford Institute for Energy Studies, 2019)
Until recently, Asian LNG contract issues, including price adjustments, have been resolved by negotiation, with few formal price review clauses, and certainly no price review arbitrations. These two, largely European phenomena to date, are only now spilling over into Asia. As this paper argues, the role of LNG price reviews and arbitrations in the Pacific Basin is likely to increase in the coming years. Asian LNG contracts finalized in the 2000s typically contain price review clauses. Contracts concluded in the recent years, which accepted a close link to oil prices in particular, are naturally exposed to price reviews. Arbitration, the preferred method of dispute resolution in European gas pricing disputes, is likely to become an important, novel, addition to the Asian LNG price review landscape. Offered with a robust, time-tested, and improved, dispute resolution mechanism, Asian LNG stakeholders they can tailor arbitration to their needs and use it primarily to hedge against the risks of protracted price review discussions.